2018
DOI: 10.1021/acs.langmuir.8b00358
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Sodium Dodecyl Sulfate at Water–Dodecane Interface in Relation to the Oil in Water Emulsion Properties

Abstract: The control of the behavior of oil in water emulsions requires deeper investigations on the adsorption properties of the emulsion stabilizers at the interfaces, which are fundamental to explain the (de)stabilization mechanisms. In this work, we present an extensive study on oil-in-water emulsions stabilized by sodium dodecyl sulfate (SDS) below its critical micellar concentration. Dynamic tensiometry, dilational rheology, and electrical conductivity measurements are used to investigate the adsorption propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 57 publications
4
30
0
Order By: Relevance
“…The two parameters values of the log-normal approximation of droplet diameter PDFs are presented in Tables 5 and 6. The interfacial tension values for the dodecane water system with several SDS concentration are taken from Llammas et al [22]. It is noted that according to the results presented and the above analysis, emulsions stability is related to both the number average diameter and the standard deviation of diameters (since these parameters determines d v ).…”
Section: Discussion and Analysis Of The Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The two parameters values of the log-normal approximation of droplet diameter PDFs are presented in Tables 5 and 6. The interfacial tension values for the dodecane water system with several SDS concentration are taken from Llammas et al [22]. It is noted that according to the results presented and the above analysis, emulsions stability is related to both the number average diameter and the standard deviation of diameters (since these parameters determines d v ).…”
Section: Discussion and Analysis Of The Resultsmentioning
confidence: 87%
“…SDS is an odorless anionic surfactant in the form of a white powder. The critical micellar concentration (CMC) of SDS is 2.5 g/L [22]. Beside the main experiments with SDS, Ethylan 1008 (AkzoNobel, 100%) is also examined in a few runs as an alternative emulsifier.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence of coalescence the droplet size distribution tends to be enlarged and moves towards larger sizes, eventually favoring creaming and destabilization of the emulsion. Among the most important effects relevant for the hindering of droplet coalescence, it is worth to mention the repulsive interaction between adsorbed layers, the interfacial coverage, the steric effects and the high dilational viscoelasticity of the interfacial layers [24,25]. The repulsive interactions are particularly relevant when ionic surfactants are concerned.…”
Section: Background On Emulsions and Droplet Interfacial Propertiesmentioning
confidence: 99%
“…The repulsive interactions are particularly relevant when ionic surfactants are concerned. In that case, it has been shown that a small amount of adsorbed molecules at the drop surface is sufficient to avoid coalescence [25] and improve remarkably the stability of emulsions. The interfacial coverage is the relative area of the interface occupied by the surfactant.…”
Section: Background On Emulsions and Droplet Interfacial Propertiesmentioning
confidence: 99%
“…There are several techniques to separate oil from water (demulsification) such as flotation [21][22][23], chemical destabilization [24], membrane separation [25][26][27], electrocoagulation [28,29] and adsorption have some advantages such as high COD removal, non-usage of chemical additives and compactness of the treatment units [30][31][32]. Adsorption is one of the most common methods for demulsification among these techniques and zeolite adsorbent has certain advantages over other conventional methods for industrial wastewater treatment [33].…”
Section: Introductionmentioning
confidence: 99%